Penney‟s game in didactics - Wilkowski, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper describes, at elementary level, Penney‟s game using the example of two players and a symmetric coin. It also provides a generalization for an unlimited number of players and coins, as an example, not an intuitive aspect of the teaching probability theory.
Didactics of Mathematics, 2013, Nr 10 (14), s. 77-86
Keywords: Penney‟s game; Conway‟s formula; probability-generating functions